The burden of disease from air pollution in Israel: How do we use burden estimates to advance public health?. Issue 1 (December 2016) - Samet, Jonathan
Abstract In an article recently published in the IJHPR, Ginsberg and colleagues from Israel's Public Health Services estimate the disease burden from airborne particulate matter in Israel. Using national data on the concentration of PM2.5 (particulate matter less than 2.5 μm in aerodynamic diameter) and risk estimates from meta-analyses, they calculate that about 2000 deaths (4.7% of total deaths) are attributable to air pollution. Although inherently subject to uncertainty, such estimates are useful for motivating public health protection and gauging the stringency of any needed regulations. However, Israel does not yet have an evidence-based process for air quality regulation comparable to that of the United States, which has evolved over the 45 years since passage of the Clean Air Act. In fact, Israel has only recently promulgated a national standard for airborne particulate matter and quantitative risk assessment has not been an element of regulatory decision-making. The report by Ginsberg and colleagues represents a useful beginning and should initiate discussion of the role of burden estimation and risk assessment more broadly in regulations intended to advance environmental health in Israel.